High Performance Liquid Chromatography (HPLC) for Detection of Glucosamine and Chondroitin Sulfate Compounds - Rakhmiyati, Rakhmiyati; Widiyani, Tetri; Budiharjo, Agung (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Glucosamine and chondroitin sulfate are compounds found in shark cartilage (Carcharhinus sorrah). The two compounds have many health benefits, that is wound healing and helping the process of angiogenesis. This study aims to determine the content of glucosamine and chondroitin sulfate compounds in shark cartilage (SC) extract. The method used was High Performance Liquid Chromatography (HPLC) with potassium phosphate buffer solution at pH 3. The results of this research were SC extract contained glucosamine and chondroitin sulfate compounds with a retention time of 1.914 minutes.